2021
DOI: 10.1136/bmjopen-2020-044815
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of quit motivation in older smokers from deprived backgrounds: a cross-sectional survey

Abstract: ObjectivesTo identify psychosocial determinants of quit motivation in older deprived smokers. The evidence may be used to optimise smoking cessation interventions for the target population.DesignCross-sectional survey using online recruitment methods including Facebook-targeted advertising.SettingUK, 2019.ParticipantsCurrent smokers aged 50 years or older and from a socioeconomically deprived background.Main outcome measuresMeasures included motivation to stop smoking, smoking history, perceived social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Results from final models suggest the most important predictors for quit success included more strongly wanting to quit to take control of one’s life, greater quitting self-efficacy, and a lower level of nicotine dependence. Current findings are supported by a recent study of older (50+ years) smokers in the general population, in which higher self-efficacy and quit confidence were cross-sectionally related with motivation to quit (Smith et al, 2021). Wanting to take control of one’s life as a reason for quitting was assessed through the endorsement of a single statement; thus, it would be helpful if future researchers could develop more psychometrically sound measures of this construct.…”
Section: Discussionsupporting
confidence: 76%
“…Results from final models suggest the most important predictors for quit success included more strongly wanting to quit to take control of one’s life, greater quitting self-efficacy, and a lower level of nicotine dependence. Current findings are supported by a recent study of older (50+ years) smokers in the general population, in which higher self-efficacy and quit confidence were cross-sectionally related with motivation to quit (Smith et al, 2021). Wanting to take control of one’s life as a reason for quitting was assessed through the endorsement of a single statement; thus, it would be helpful if future researchers could develop more psychometrically sound measures of this construct.…”
Section: Discussionsupporting
confidence: 76%
“…Other questions, such as social networks and comorbid conditions, were identified as relevant in the field of smoking and smoking cessation for the target population. 15 The topic guide was pilot tested on a member of the public from a low SE background who had a smoking history. Open discussions were invited on (1) delivery of stop-smoking support as part of LCS and reasons for declining stop-smoking support; (2) views on stopping smoking and their current motivation to quit using the Motivation to Stop Scale 29 , 30 ; (3) self-efficacy in relation to quitting smoking; (4) previous quit attempts; (5) impact of their social network on smoking behaviors; and (6) any comorbid conditions that may impact their motivation to quit smoking.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research conducted with individuals who have a smoking history and are from a low SE background has shown that there are multiple complex barriers that may influence motivation to stop smoking including high levels of nicotine dependence, lack of confidence for quitting, low perceived effectiveness of Stop Smoking Services (SSS), risk-minimizing beliefs related to smoking-related diseases, and pre-existing physical and mental health issues. 15–19 A further factor that may hinder smoking cessation and motivation to stop-smoking attempts in the high-risk, lung screening-eligible population is a lack of social support. People who smoke from lower SE groups report negative experiences when trying to quit, including a lack of support during previous quit attempts.…”
Section: Introductionmentioning
confidence: 99%
“…Specialist lung screening SCPs could adopt a flexible, person-centred approach to the offer and delivery of SBP cessation support, enabling tailored support based on quit motivation, the lung screening context and wider determinants of health in the high-risk population typically experiencing long-term tobacco dependence. 13 A buffer period between screening attendance and quit date can be used to increase participants' interest and confidence in using NRT prior to abrupt cessation, particularly for participants not considering quitting at the time of screening. However, maintaining, delivering and monitoring the high standards of SBP delivered within this study may be challenging in a real-world setting.…”
Section: Discussionmentioning
confidence: 99%
“…12 The prevalence of high nicotine dependence and socioeconomic deprivation among lung screening-eligible individuals presents multi-factorial challenges to quitting smoking, reiterating the need for high-intensity approaches in this population. 13 The Yorkshire Enhanced Stop Smoking (YESS) study 14 evaluated the effectiveness of an opt-out, colocated standard best practice (SBP) smoking cessation service within the Yorkshire Lung Screening Trial (YLST 15,16 ) versus SBP plus a booklet intervention (Figures 1&2). SBP, in line with National Centre for Smoking Cessation standards, consisted of point-of-care behavioural support, pharmacotherapy and 12-weeks of ongoing support with smoking cessation practitioners (SCPs).…”
Section: Introductionmentioning
confidence: 99%